EFFICACY OF BIOAPIGYN OINTMENT FOR PELVIC MUSCLE TONUS IN THE TREATMENT OF STRESS URINARY INCONTINENCE AND VULVOVAGNAL DISORDERS - Višnja, Oreščanin; Štefica, Findri Guštek; Ivan, Fistonić; Josipa, Rodić (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Objectives: The purpose of this work was development, formulation and testing of new herbalointment for the treatment of stress urinary incontinence and its related symptoms andcomparison of its efficiency with the results of pelvic muscle training. The influence of thetreatment or training onto vulvo-vaginal disorders was also determined.Materials and methods: 132 women in the age range from 32 to 77 years were randomlyselected into experimental and control group. The experimental group was treated two weekswith Bioapigyn ointment for pelvic muscle tonus (2 g/day) which consisted of the followingingredients: honey; glycerol, Cera flava, oil macerates of the plants Capsella bursa-pastoris,Urtica diodica, Quercus robur, Salvia officinalis, Achillea millefolium, Alchemilla vulgaris,Calendula officinalis, Matricaria chamomilla, Plantago major; essential oils of the plantsMelaleuca alternifolia, Thymus vulgaris ct. tymol, Origanum vulgare. Control group wassubjected to pelvic muscle training during 24 weeks (three times a week). The degree ofincontinence and its impact on the quality of life prior and after the treatment or training wasassessed by the International Consultation on Incontinence Questionnaire - Urinary IncontinenceShort Form (ICIQ-UI SF), where maximum score of 21 represents permanent incontinence and 0no leakage of urine. The volume of residual urine, perineometry and vaginal pH were alsodetermined before and after the treatment or training. For statistical evaluation STATISTICA11.0 package was used.Results: The variables with the highest, statistically significant influence onto degree ofincontinence and its impact on the quality of life were body mass index and menopause.Significant decrease following the treatment with Bioapigyn ointment was found for ICIQ-UI SFscore (from 12.43±4.83 to 8.61±4.92, p<0.00001), residual urine volume (from 8.73±11.18 to2.78±5.93 mL, p=0.0002) and vaginal pH (from 6.30±0.63 to 5.59±0.50, p= 0.0000). The increasein the muscle strength was also confirmed. In the end of the treatment all the symptoms ofvulvo-vaginal disorders disappeared completely in all 66 participants. Control group alsoshowed some improvement in the values of ICIQ-UI SF score, residual urine and perineometryresults. However, those changes were not statistically significant. There was no improvementconcerning the vaginal pH and the symptoms of vulvo-vaginal disorders.Conclusion: Preliminary study confirmed the efficiency of Bioapigyn ointment for pelvic muscletonus in the treatment of stress urinary incontinence as well as the symptoms of vulvo-vaginaldisorders due to its components with smooth muscle contraction activity, uterotonic activity aswell as pH adjusting, coating, moisturizing and soothing effect. Significantly better results formost of the variables were found in the experimental compared to the control group.